Patient Adherence to Tuberculosis Treatment: A Relation between Family Support and Patient Behavior - Rani Putri Haji Soleman; Tintin Sukartini; Arina Qona'ah (Critical Medical and Surgical Nursing Journal (CMSNJ), 2021)
Introduction: Knowledge, family support, and behavior have a significant impact on an individual's and community's health. They play a critical part in deciding disease control programs and transmission prevention of tuberculosis. The purpose of the study was to determine the association between family support, patient behavior, and tuberculosis treatment compliance in the Baing Primary Health Care of Wulla-Waijilu DistrictMethods:The study design was cross-sectional using the Spearman Rho test. The sample was 123 respondents with purposive sampling technique. The data collection was using sociodemographic questionnaires, family support, behavior, TB treatment adherence and MMAS-8. The dependent variable in this study was family support. The independent variables in this study were patient behavior and TB treatment adherence.Result:There was a relationship between family support and patient behavior (p=0.025), a relationship between family support and compliance with TB treatment (p=0.042)Conclusion:It can be concluded that there was a relationship between family support and TB patient behavior and there was a strong and significant relationship between family support and the level of TB treatment adherence.